ANALISIS PENGARUH DAERAH PEMASOK TERHADAP HARGA CABAI MERAH DI DKI JAKARTA MENGGUNAKAN VECTOR ERROR CORRECTION MODEL (VECM) - Erwandi Erwandi; Farit Mochamad Afendi; Budi Waryanto (Statistics and Data Science Program Study, SSMI, IPB University, in collaboration with the Forum Pendidikan Tinggi Statistika Indonesia (FORSTAT) and the Ikatan Statistisi Indonesia (ISI), 2019)
This study aims to analyze the effect of red chili price and production in the supplier area on its prices in DKI Jakarta using the Vector Error Correction Model (VECM). The data used in this study are red chili price and average expenditure per month per capita in DKI Jakarta and red chili price and production in East Java, West Java, and Banten in the period January 2012 to July 2018. The model obtained was VECM (1) the price of red chili in DKI Jakarta. It showed that there was a long-term relationship (cointegration) on the first difference. The results the Forecast Error Variance Decomposition (FEVD) analysis showed that the contributions of the red chili price in DKI Jakarta and West Java, average monthly expense for red chili in DKI Jakarta, red chili production (West Java and Banten) are significant in explaining the behaviour of the red chili price change in DKI Jakarta. The results of the Impulse Response Function (IRF) analysis showed that the shock of the price of chili in DKI Jakarta and West Java in the previous month will increase the price of red chili in DKI Jakarta in the following month. Conversely, the shock of the average monthly expenditure of red chili in DKI Jakarta and red chili production (West Java and Banten) from the previous month will reduce the price of red chili in DKI Jakarta in the following month.